El Estado chileno y la región de la Frontera a fines del siglo XIX - Arauco Chihuailaf (Les Cahiers ALHIM)
At the end of the 19th, country to what occurs in the Chile of then, the presence of the State is not yet consolidated in the Araucania. Araucania or border was conquered but still controlled territory indeed. The State will gradually be consolidated thanks to the construction of the railway, the land, colonization, the foundation of cities. This process of occupation of the mapuche historical territory produce accelerated changes: landscape, ownership of the land, of the population, will lead to a global consolidation of the State: economic, political, and administrative.